Jordanian News Portals’ Coverage of 4th Circle Protests (2018): A Comparative Analytical Study - Shakhanbeh, Zeyad (Dirasat: Human and Social Sciences, 2021)
The aim of this research is to identify the most prominent words, ideas and contents of the Jordanian news websites in their coverage of the "Fourth of June 2018 protests" and to identify the differences between them according to their ownership in their dealings with popular issues. The analysis was based on a descriptive analytical approach using a content analysis tool and a comparative approach to identify the differences between the contents. The analysis form included (6) analytical categories in which the coverage of these protests and their topics was analyzed by applying a comprehensive survey of all news and reports (102), And a report published by a sample of Jordanian news websites: Hala Akhbar, Al-Rai, and Nissan, JO24, from 30/5 to 8/6/2018, and the location of these protests in the center of the Jordanian capital (Amman). The research reached several results, the most important of which are: 1- The most frequent words of government-related protests were the word "overthrow". 2- The most frequent words of the tax-related protests were the word "withdrawal". 3- The most frequent words for protesters are the word "protests". 4- The most frequent words related to the "security forces" are the word "aggression". 5- The most frequent words of "management of the general approach in the State" are the word "economy". 6- The four sites did not care to publish the word "corruption" in a manner suitable for calling for protests